Exploring EFL Secondary Learners’ Emotional Engagement On Kahoot as A Game-Based Response System - Sarah Wahyuni; Dadang Danugiri; Muhammad Reza Pahlevi (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
The purpose of this study is to discover how Kahoot emotionally engages students’ feelings in the EFL classroom. The research was conducted to one of senior high in Pebayuran which included five students from MIPA’s tenth grade. This research uses descriptive case study as research design. The data is gathered through semi-structured interviews, questionnaires, and documentation. The interview has been done via WhatsApp call. The questionnaire was distributed via a WhatsApp group and using a 5-point Likert scale. The documentation is a photograph of students in learning activities. This study employed thematic analysis which included six steps to analyze the data. Those six steps are familiarizing the data, generating initial codes, searching for themes, reviewing themes, defining and naming data, and producing the report. As a result, it was found that Kahoot positively engages students' emotionally. It presented that Kahoot makes the learning joyful, students felt enjoy, interested, happy, motivate, and enthusiastic. However, there are challenges in using Kahoot. It found that students’ anxiety of limited times and technical problems of internet connection.